The comparison of size-specific dose estimate in CT examination based on head and body PMMA phantom - Mohd Hanafi Ali; Choirul Anam; Freddy Haryanto; Geoff Dougherty (Diponegoro University Semarang Indonesia, 2018)
Nowadays, a dose estimate for individual patients undergoing CT examination is carried out using the metric of size-specific dose estimate (SSDE), which is calculated by multiplying a volume CT dose index (CTDIvol) and a correction factor that is a function of patient size. Two CTDIvol values are based on head and body PMMA phantoms. There are also two values of correction factors (k), both for head and body PMMA phantoms. The purpose of this study was to compare the SSDE values calculated using head and body PMMA phantoms with their corresponding correction factors (k). The CTDIvol values were derived from the ImPACT 1.04 software for 12 CT scanners: Sensation 4, Sensation 16, Sensation 64, Light Speed, Light Speed 16, Light Speed VCT, Secura, Brilliance 16, Brilliance 64, Asteion Dual, Aquilion 4, and Aquilion 16. The size of the patients who underwent CT examination was characterized by a water-equivalent diameter (Dw) from 10 cm to 45 cm. The results indicated that the differences in SSDE values based on head and body CTDIvol were within 20%. Thus, the SSDE value can be calculated using the head or body CTDIvol bases with corresponding k value.